2002
DOI: 10.1111/j.1745-7599.2002.tb00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Pediatric Obesity: Assessment and Management in the Primary Care Setting

Abstract: Pediatric obesity has risen dramatically in the United States during the last two decades; it is a significant child health problem that is preventable and largely under-diagnosed and under-treated. It is essential to discuss prevention of obesity with parents at every well-child visit; treatment should be initiated when patterns of weight gain exceed established percentiles for increasing height for age and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…A literature review about this issue has concluded that childhood obesity is largely under-diagnosed and under-treated in the primary health care systems. [26] It will be essential to integrate the education about the underweight-overweight phenomenon in the curriculum of different levels of health care workers.…”
Section: Original Articlementioning
confidence: 99%
“…A literature review about this issue has concluded that childhood obesity is largely under-diagnosed and under-treated in the primary health care systems. [26] It will be essential to integrate the education about the underweight-overweight phenomenon in the curriculum of different levels of health care workers.…”
Section: Original Articlementioning
confidence: 99%
“…In the resiliency model, families respond to stressful life events by a transition of adjusting and adapting. Conversely, maladaptive responses to stress place families at risk for outcomes such as depression, violence, substance abuse, and nicotine dependence (Anderson, Roux, & Pruitt, 2002;McCubbin & McCubbin, 1993;Nichols, 1999) or obesity in parents and children (Nichols & Livingston, 2002).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Small samples, varied interventions and follow-up periods were reflected in most of the research conducted during those years. Specific issues included the overall limited success of weight loss interventions, which was often related to the short duration of the interventions, cost, or a lack of interest from members of the family regarding participation (Nichols, Livingston, & Schumann, 2002). Interestingly, nurses were rarely mentioned as members of the interdisciplinary research teams developing and implementing those intervention studies.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews of childhood overweight or obesity focused on a variety of single potentially important influencing factors including parental involvement (Pinquart, 2014;Yavuz, Van Ijzendoorn, Mesman, & Van der Veek, 2014), schoolbased studies (Gonzalez-Suarez, Worley, Grimmer-Somers, & Dones, 2009;Lavelle, Mackay, & Pell, 2012;Sobol-Goldberg, Rabinowitz, & Gross, 2013), and types of treatment (Ho et al, 2013;Perez-Morales, Bacardi-Gascon, & Jimenz-Cruz, 2012), among others. However, no meta-analysis was found which, in addition to examining weight loss, focused on intervention studies conducted in other countries in over a decade (2002( -September 2015, the nurse's role within interdisciplinary teams conducting this research, or the cost of the interventions.…”
Section: Introductionmentioning
confidence: 99%